2021
DOI: 10.1007/s00466-021-02080-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-field formulations for isogeometric Reissner–Mindlin plates and shells with global and local condensation

Abstract: In this paper, mixed formulations are presented in the framework of isogeometric Reissner–Mindlin plates and shells with the aim of alleviating membrane and shear locking. The formulations are based on the Hellinger-Reissner functional and use the stress resultants as additional unknowns, which have to be interpolated in appropriate approximation spaces. The additional unknowns can be eliminated by static condensation. In the framework of isogeometric analysis static condensation is performed globally on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In order to counteract the different locking phenomena that can occur while solving linear elasticity problems using common finite element formulations, various methods can be employed [1,2]. Particularly, this comprises higher order formulations or mixed methods [3][4][5]. As a result, the computational effort is increased.…”
Section: Introductionmentioning
confidence: 99%
“…In order to counteract the different locking phenomena that can occur while solving linear elasticity problems using common finite element formulations, various methods can be employed [1,2]. Particularly, this comprises higher order formulations or mixed methods [3][4][5]. As a result, the computational effort is increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, when applied to structural theories that take into account transverse shear deformations, spline-based discretizations suffer from the same types of locking as conventional FEA discretizations based on Lagrange polynomials. [19][20][21] Thus, spline-based discretizations of curved Timoshenko rods [22][23][24][25][26] and Reissner-Mindlin shells [27][28][29][30][31] are adversely affected by shear and membrane locking. Shear and membrane locking lead to displacements, rotations, and bending moments with smaller values than expected and shear and membrane forces with large-amplitude spurious oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have shown that the problem can be solved or alleviated by using higher-order finite-element methods or adding special locking treatments to lower-order methods. The typical locking treatment approaches, which may not be restricted to solid-shell elements, include assumed natural strains (ANS), 18,19 enhanced assumed strain (EAS), 20 discrete strain gap (DSG), 21 B-method, [22][23][24][25] mixed formulations, 22,[26][27][28] selective/reduced integration, 26,[29][30][31] and projection techniques based on the moving least square (MLS). 32 Extensive literatures have reported that shells are studied by kinds of numerical methods: the finite element method (FEM), [33][34][35] the meshfree method, [36][37][38][39] and analytical 40,41 or semianalytical 42,43 methods and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have shown that the problem can be solved or alleviated by using higher‐order finite‐element methods or adding special locking treatments to lower‐order methods. The typical locking treatment approaches, which may not be restricted to solid‐shell elements, include assumed natural strains (ANS), 18,19 enhanced assumed strain (EAS), 20 discrete strain gap (DSG), 21 trueB‐method, 22–25 mixed formulations, 22,26–28 selective/reduced integration, 26,29–31 and projection techniques based on the moving least square (MLS) 32 …”
Section: Introductionmentioning
confidence: 99%